Cranioplasty Using Autologous Fasciae Latae Graft for Nasal Bone Fracture Repair in a Dog - Ferreira, Annalú Pinton; Oliveira, Alana Lucena; Mostachio, Giuliano Queiroz; Ferreira, Joana Zafalon; Fernandez, Stephanie; Souza, Talita Floering Brêda; de Nardi, Andrigo Barboza; Rossetto, Victor José Vieira (Acta Scientiae Veterinariae, 2017)
Background: In facial reconstruction, several kinds of grafts can be used, like bone grafting, cutaneous grafting, biological membranes, fasciae latae, biomaterials, and others. The advantage of using fasciae latae in the tissue reparation is the need of little blood supply, making it a viable option in the restoration of biological functions. The objective of this study was to describe the case of a female poodle, 12-year-old, and with subcutaneous emphysema due to fracture of the nasal bone, submitted to cranioplasty using fasciae latae. Case: It was attended a 12-year-old female poodle due to a traumatic brain injury. At physical examination, the animal had presented facial swelling and respiratory distress with inspiratory effort. Additionally, were verified subcutaneous emphysema and a depression in the nasal plane region with crepitus on palpation. Radiographic examinations revealed nasal bone and maxilla fractures. The animal was submitted to cranioplasty for nasal bone fracture repair. To access the nasal bone and frontal sinus was performed an incision in the dorsal midline from the level of medial orbital rim to the nasal plane. The subcutaneous tissue was divulsioned to allow the exposure of the nasal bone fracture, whose small fragments prevented the internal fixation. The bone defect was then repaired using free autologous fasciae latae of 2 cm wide x 3 cm long, sutured to the periosteum. Subcutaneous emphysema gradually decreased until its resolution at three days postoperatively. The surgical wound had complete healing at 10 days after surgery without concomitant complications. Discussion: The choice of the reconstructive technique is based on the operative planning and the surgeon’s experience. In the present case we opted for the autologous fasciae latae graft since its ready availability and lesser predisposition to immunogenic sensibilization and rejection. In addition, we opted for the autologous fasciae latae graft because it is an occlusive material that would prevent the air flow through it during the inspiration and expiration, and consequently the aggravation of the subcutaneous emphysema. In fact, the resolution of the subcutaneous emphysema occurred three days after grafting. Furthermore, the resolution of the subcutaneous emphysema was determined by the lower retraction of the autologous fasciae latae graft due to the scar fibrous tissue deposition. The choice of the reconstructive technique is also based on the viability of the recipient bed, which should provide adequate blood supply for the reception of the free graft. In the present case, however, the bone defect did not provide adequate blood supply and structural support. Due to this, the autologous fasciae latae graft was crucial to the verified results, since it requires less blood supply and structural support to remain the graft viable. We concluded that the autologous fasciae latae graft may be a viable option for the anatomical and functional reconstruction of traumatic lesions localized in the skull, particularly the nasal bone, due to the satisfactory follow-up in the present case without the occurrence of complications. A larger sample size, however, it is necessary to evaluate the real effectiveness of the autologous fasciae latae graft in reconstructive skull surgery on small animals.